2014
DOI: 10.1128/aac.02472-14
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Pf mdr1 , Pf crt , and Pf nhe1 Genes Are Associated with Reduced In Vitro Activities of Quinine in Plasmodium falciparum Isolates from Western Kenya

Abstract: bIn combination with antibiotics, quinine is recommended as the second-line treatment for uncomplicated malaria, an alternative first-line treatment for severe malaria, and for treatment of malaria in the first trimester of pregnancy. Quinine has been shown to have frequent clinical failures, and yet the mechanisms of action and resistance have not been fully elucidated. However, resistance is linked to polymorphisms in multiple genes, including multidrug resistance 1 (Pfmdr1), the chloroquine resistance trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…Furthermore, the preliminary data indicate that treatment with quinine selected for pfcrt 76T among recrudescing P. falciparum. Other studies have indicated that pfcrt is involved in the transport of quinine and that SNPs in pfcrt, including 76T, decrease P. falciparum susceptibility to quinine (22,(33)(34)(35). Thus, it seems highly probable that the increased pfcrt 76T frequency was due to the increased use of quinine.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the preliminary data indicate that treatment with quinine selected for pfcrt 76T among recrudescing P. falciparum. Other studies have indicated that pfcrt is involved in the transport of quinine and that SNPs in pfcrt, including 76T, decrease P. falciparum susceptibility to quinine (22,(33)(34)(35). Thus, it seems highly probable that the increased pfcrt 76T frequency was due to the increased use of quinine.…”
Section: Discussionmentioning
confidence: 96%
“…The increased TN haplotype might be due to direct selection by quinine. However, decreased quinine susceptibility has more often been linked with the TY haplotype (22,35). The discrepancy may be due to the probable multigenic basis of quinine resistance (22,37).…”
Section: Discussionmentioning
confidence: 99%
“…Between 2010 and 2012 QN was prescribed to 44% of children diagnosed with P. falciparum malaria [236]. Several studies have linked pfcrt 76T to decreased QN susceptibility [168,[262][263][264]. In line with this, the pfcrt 76T frequency was higher amongst recrudescing P. falciparum compared to day 0 after treatment with QN in Guinea-Bissau [236].…”
Section: Real-time Pcrmentioning
confidence: 90%
“…In line with this, the increase of pfcrt 76T + pfmdr1 86N between 2007 and 2012 in Guinea-Bissau could be due to direct selection by QN. However, decreased QN susceptibility has more often been linked with the TY haplotype[168,264]. The discrepancy may be due to the probably multigenic basis of QN resistance[75,168].…”
mentioning
confidence: 99%
“…Further, we observed significant association of increased pfmdr 1 gene expression with reduced in vitro drug susceptibility to amodiaquine and piperaquine. Based on molecular markers, studies have shown chloroquine resistance remains high in western Kenya 29 30 . Amodiaquine, chloroquine and piperaquine are in the 4-aminoquinoline drug family, which might explain the significant association seen of increased pfmdr 1 gene expression with reduced in vitro susceptibility to amodiaquine and piperaquine.…”
Section: Discussionmentioning
confidence: 99%